Effects of daily life changes due to COVID-19 on obesity in Korean adults. - Jeon, Hee-Min; Han, Mi Ah; Park, Jong; Ryu, So Yeon (Journal of Public Health, 2025)
Background Owing to the changes in lifestyle caused by the COVID-19 pandemic, the risk of obesity has increased. This study analyzed the relationship between daily life changes due to COVID-19 and obesity among Korean adults. Methods This study used data from the 2021 Korea Community Health Survey. A total of 225 265 Korean adults had completed the survey. The associations between general, health-related, and COVID-19-related characteristics and obesity were analyzed using Chi-square tests and multiple logistic regression analyses. Results The obesity rate among the total participants was 30.6%. Among all participants, 18.7% responded that COVID-19 had a significant impact on their daily lives. The obesity was higher in cases where the impact of COVID-19 on daily life was significant, concerns about economic damage due to COVID-19 were present, and changes in expenditure had occurred. In addition, obesity rates were higher in participants who experienced decrease in physical activity, increase in instant food consumption, and increase in smoking after COVID-19. Conclusions COVID-19 has brought about significant changes in daily life, including physical activity and eating habits. Our study suggests that these changes in daily life due to COVID-19 may associate the risk of obesity.